Metal Complexes of Diisopropylthiourea: Synthesis, Characterization and Antibacterial Studies - Ajibade, Peter A. (Molecular Diversity Preservation International (MDPI), 2011)
Co(II), Cu(II), Zn(II) and Fe(III) complexes of diisopropylthiourea have been synthesized and characterized by elemental analyses, molar conductivity, magnetic susceptibility, FTIR and electronic spectroscopy. The compounds are non-electrolytes in solution and spectroscopic data of the complexes are consistent with 4-coordinate geometry for the metal(II) complexes and six coordinate octahedral for Fe(III) complex. The complexes were screened for their antibacterial activities against six bacteria: Escherichia coli, Pseudomonas auriginosa, Klebsiella pneumoniae, Bacillus cereus, Staphylococcus aureus and Bacillus pumilus. The complexes showed varied antibacterial activities and their minimum inhibitory concentrations (MICs) were determined.